2022
DOI: 10.1111/bpa.13106
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and oxidative stress markers in intracerebral hemorrhage: Relevance as prognostic markers for quantification of the edema volume

Abstract: We aimed to analyze the inflammatory and oxidative stress (OS) markers after intracerebral hemorrhage (ICH) and their temporal changes, interaction effects, and prognostic values as biomarkers for the prediction of the edema volume. Our prospective, longitudinal study included a cohort group of 73 conservatively treated patients with ICH, without hematoma expansion or intraventricular bleeding, which were initialized with the same treatment and provided with the same in-hospital care during the disease course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Vladimir et al showed a close correlation between NLR and neuroimaging markers (hematoma volume, especially edema volume) in their study. [9] Similar results were obtained in our research. After further analysis, we found that admission NLR could be a predictor of early PHE growth.…”
Section: Discussionsupporting
confidence: 91%
“…Vladimir et al showed a close correlation between NLR and neuroimaging markers (hematoma volume, especially edema volume) in their study. [9] Similar results were obtained in our research. After further analysis, we found that admission NLR could be a predictor of early PHE growth.…”
Section: Discussionsupporting
confidence: 91%
“…NLR was usually considered as a sensitive marker for severity of diseases, such as cancer, infection, and stroke 15,37,38 . In ICH patients, NLR and ANC were synergistically on propagation of the inflammatory cascade which enhanced the IL‐6 effects on the edema volume 39 . In experimental BGH, neutrophil infiltration with the high level of IL‐6 and IL‐1β was obvious in the intestine and blood circulation in acute stage 6,40 .…”
Section: Discussionmentioning
confidence: 99%
“…15,37,38 In ICH patients, NLR and ANC were synergistically on propagation of the inflammatory cascade which enhanced the IL-6 effects on the edema volume. 39 In experimental BGH, neutrophil infiltration with the high level of IL-6 and IL-1β was obvious in the intestine and blood circulation in acute stage. 6,40 It suggested that these activated cytotoxic factors played the important role in gut mucosal damage and barrier dysfunction.…”
Section: Ta B L E 2 Predictive Capability Of Inflammatory Markers For...mentioning
confidence: 94%
“…An elevated NLR value usually means an increase in neutrophils (reflecting a proinflammatory state) and/ or a decrease in lymphocytes (reflecting the weak adaptive immunity to diseases). Therefore, NLR has been suggested to predict the severity and mortality of various diseases, such as sepsis [7], community-acquired pneumonia [8,9], chronic obstructive pulmonary disease [10,11], acute limb ischemia [12], acute cholecystitis [13], cardiovascular disease [14][15][16], and intracerebral hemorrhage [17,18], as well as the recent pandemic COVID-19 pneumonia [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%